Women's perceptions of contraceptive efficacy and safety - Roshni Kakaiya; Lia L. Lopez; Anita L. Nelson (BMC, 2017)
Abstract Background Adoption of contraceptive implants and intrauterine devices has been less than might be expected given their superior efficacy and convenience. The purpose of this study was to assess knowledge and beliefs held by women, which may influence their contraceptive choices and theirongoing utilization of contraceptive methods. Methods English speaking, nonpregnant, reproductive-age women, who were not surgically sterilized, were individually interviewed to obtain limited demographic characteristics and to assess their knowledge about the efficacy of various contraceptive methods in typical use and about the relative safety of oral contraceptives. Results A convenience sample of 500 women aged 18-45 years, with education levels that ranged from middle school to postdoctoral level was interviewed. The efficacy in typical use of both combined oral contraceptives and male condoms was correctly estimated by 2.2%; over two-thirds of women significantly overestimated the efficacy of each of those methods in typical use. Oral contraceptives were thought to be at least as hazardous to a woman's health as pregnancy by 56% of women. Conclusions The majority of reproductive aged women surveyed substantially overestimated the efficacy of the two most popular contraceptive methods, often saying that they were 99% effective. Women with higher education levels were most likely to overestimate efficacy of oral contraceptives. Women of all ages and education levels significantly overestimated the health hazards of oral contraceptives compared to pregnancy. Overestimation of effectiveness of these methods of contraception, may contribute to lower adoption of implants and intrauterine devices. When individualizing patient counselling, misperceptions must be identified and addressed with women of all educational backgrounds. Trial registration Not applicable.